1978
DOI: 10.1902/jop.1978.49.10.495
|View full text |Cite|
|
Sign up to set email alerts
|

The Induction of New Bone and Cementum Formation: IV. Microscopic Examination of the Periodontium Following Human Bone and Marrow Allograft, Autograft and Nongraft Periodontal Regenerative Procedures.

Abstract: This retrospective study based on histologic evaluations of 100 human block sections and extracted teeth taken from sites treated via bone and marrow autograft, allograft and nongraft regenerative procedures revealed the following findings: 1. Graft procedures yielded new cementum formation in 66 of 79 sites evaluated while nongraft approaches yielded new cementum formation in only 7 of 21 sites. Two of the grafted sites not yielding new cementum were only 14 days duration. 2. Block section evaluation revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(58 citation statements)
references
References 11 publications
0
55
0
3
Order By: Relevance
“…8 Use of demineralized freeze-dried bone allograft overcomes many of the problems associated with autografts, but these materials are human products procured from banks; hence, there is a small but measurable risk of disease transmission estimated at one in 1 million to one in 8 millions. 9 Among various herbal medicaments, the paste and extract of CQ has been used for its potential as a bone regenerative material. Udupa et al 10 conducted a study by applying plant extract on the fractured bones of dogs and found a marked difference in the progress of endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…8 Use of demineralized freeze-dried bone allograft overcomes many of the problems associated with autografts, but these materials are human products procured from banks; hence, there is a small but measurable risk of disease transmission estimated at one in 1 million to one in 8 millions. 9 Among various herbal medicaments, the paste and extract of CQ has been used for its potential as a bone regenerative material. Udupa et al 10 conducted a study by applying plant extract on the fractured bones of dogs and found a marked difference in the progress of endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…En 1976, se realiza una serie de refl exiones sobre las técnicas de injertos (14), según Melcher, la hipótesis de Hiatt y colaboradores era parcial, ya que estaba limitada sólo a la regeneración ósea (15). Para este autor, la regeneración del ligamento periodontal era una cuestión fundamental, ya que es el tejido que da continuidad entre el hueso y el cemento, y que además contiene células las cuales pueden sintetizar y remodelar los tres tejidos de origen mesenquimal que forman el periodonto.…”
Section: Regeneracion Tisular Guiada (Rtg)unclassified
“…Durante casi 50 años, la atención de los investigadores se centró en regeneración ósea, y que la formación de hueso nuevo induce a la formación de nuevo cemento y ligamento periodontal (15). Bajo esta premisa, diferentes tipos de injertos de hueso y otros materiales se han utilizado, los cuales, de acuerdo con su origen, se han clasifi cado como: autoinjertos (obtenido del mismo paciente), aloinjerto (la misma especie pero diferente individuo), los xenoinjertos (injertos de diferentes especies) y aloplásticos (material sintético o injerto de un cuerpo extraño).…”
Section: Regeneracion Tisular Guiada (Rtg)unclassified
“…The best way to resolving this problem is to carry out guided bone regeneration (GBR) prior to implant treatment [1][2][3] . The gold standard for osteoplasty is autologous bone grafting, using bone harvested from inside or outside the mouth as a graft 4) . However, this has the disadvantages of requiring two-stage surgery, postoperative impairment of the donor site, limitations on the amount of bone that can be harvested, and rapid resorption of autologous bone.…”
Section: Introductionmentioning
confidence: 99%